El control judicial de la regulación económica y el margen de deferencia en Estados Unidos: el fin del precedente Chevron - Hernández G, José Ignacio (2025)
In 2024, the United States Supreme Court overturned a landmark precedent, Chevron, which was initially adopted in 1984. Chevron had been the general doctrine used to define the scope of judicial review over regulatory agencies, based on deferential control over vague concepts established in statutes. However, in Loper Bright, the Court concluded that this deferential control was incompatible with judicial review. It is important to note that the Court did not challenge the constitutionality of the modern administrative state. The Supreme Court also acknowledged that courts should adopt a deferential review when a statute grants discretionary powers. Despite this, the Court ratified that agencies can only adopt regulations with vast economic and social impact upon express delegation of the statute. This could lead to the potential denial of any deferential review, advancing in the constitutional crisis of the modern administrative state due to the practical obstacles that impede Congress from exhausting vast regulations in statutes.